TESTING OF SHEEP POX VIRUS VACCINE IN SHEEP UNDER EXPERIMENTAL AND EPIZOOTIC CONDITIONS - V. I. Diev; S. K. Starov; D. K. Basova; V. Yu. Kulakov; A. V. Konstantinov (Ветеринария сегодня)
Antibodies were shown in blood of lambs vaccinated once with anti-sheep pox virus vaccine based "ARRIAH" strain at the age of one, two and three months and their titres were age-dependant. It was demonstrated that the sheep were resistant to the disease if their mean postvaccinal virus neutralizing antibody titres were within (1.75 ± 0.16)-(2.34 ± 0.24) log2. The regression models characterizing relationship between humoral factor levels and protective function of anti-sheep pox virus immunity in sheep were constructed. It was determined that 78% and 91% of animals in the flock should be seropositive with mean antibody titres of 1.43 log2 and 1.97 log2 to ensure protection of 80% and 95% of immunized animals, respectively.